KOOPERATIVES MITEINANDER STATT NEBENEINANDER. ZUR BEZIEHUNG ZWISCHEN DER INTERKULTURELLEN FREMDSPRACHENDIDAKTIK UND DEN KULTURWISSENSCHAFTEN - Adamczak-Krysztofowicz, Sylwia (Wydawnictwo Naukowe UAM, 2005)
The goal of developing the learner's intercultural communicative competence can best be achieved by an intercultural approach of foreign language teaching encompassing both the acquisition of linguistic and cultural competence as well as combining cognitive, communicative and affective goals to learning languages. In the field of intercultural foreign language teaching research, however, the most recent findings in cultural studies can influence effective methods of developing intercultural communicative competence. The aim of the article is therefore to focus on the importance of different cultural disciplines, examing their connections with cognitive and affective goals of foreign language teaching. The conclusive part of the paper points at issues that can become the object of further glottodidactic research.
Keywords: Fremdsprachedidaktik; Kulturwissenschaften